2012
DOI: 10.1136/bjsports-2012-091078
|View full text |Cite
|
Sign up to set email alerts
|

The role of haemoglobin mass on VO2max following normobaric ‘live high–train low’ in endurance-trained athletes

Abstract: It remains unclear by which mechanism 'live high-train low' (LHTL) altitude training increases exercise performance. Haematological and skeletal muscle adaptations have both been proposed. To test the hypotheses that (i) LHTL improves maximal oxygen uptake (VO(2)max) and (ii) this improvement is related to hypoxia-induced increases in total haemoglobin mass (Hb(mass)) and not to improved maximal oxidative capacity of skeletal muscle, we determined VO(2)max before LHTL and after LHTL, before and after the altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…In that study male (VO 2 max=73.1) and female (VO 2 max=64.4) runners completed 2×3-week blocks of 14 h/day, 3000 m LHTL in a controlled but non-blinded manner. It was concluded that there is a large individual variation in the change in physiological and performance measures (as also noted by others,29 30 but that normobaric LHTL induces reproducible mean improvements in VO 2 max and RCV Changes in time trial performance varied considerably more. The specific reason for the individual variation still remains to be elucidated, and further research in line with this is encouraged and could include studies on the potential interactions between nHb and [Hb], central circulatory changes including a hypoxia-dependent reduction of maximal heart rate,31 differences in protein synthesis and degradation32 and differences in buffer capacity 33 34…”
Section: Introductionmentioning
confidence: 55%
“…In that study male (VO 2 max=73.1) and female (VO 2 max=64.4) runners completed 2×3-week blocks of 14 h/day, 3000 m LHTL in a controlled but non-blinded manner. It was concluded that there is a large individual variation in the change in physiological and performance measures (as also noted by others,29 30 but that normobaric LHTL induces reproducible mean improvements in VO 2 max and RCV Changes in time trial performance varied considerably more. The specific reason for the individual variation still remains to be elucidated, and further research in line with this is encouraged and could include studies on the potential interactions between nHb and [Hb], central circulatory changes including a hypoxia-dependent reduction of maximal heart rate,31 differences in protein synthesis and degradation32 and differences in buffer capacity 33 34…”
Section: Introductionmentioning
confidence: 55%
“…We also suggest that in comparison with the heat acclimatisation-induced effects, the 3% increase in Hb mass in the HYP group was too small to substantially alter more both maximal oxygen uptake and high-intensity running performance 39. This conclusion is further reinforced by the blinding of the players toward the intervention (ie, for sleeping and cycle interval training), so that a placebo effect during the post-tests was unlikely in the HYP group 40 41.…”
Section: Discussionmentioning
confidence: 86%
“…Also, as the magnitude of haemoglobin (Hb) increase has been suggested to be related to baseline Hb mass ,102 team-sport athletes may be more likely to present increased Hb mass in response to AT than elite cyclists. Even though increases in Hb mass do not necessarily lead to improvements in VO 2max ,99 there may be benefits for aerobic metabolism through the compensatory decrease in blood flow which may slow the mean blood transit time and improve the exchange of gases, substrates and metabolites 103.…”
Section: Introductionmentioning
confidence: 99%